2018
DOI: 10.1039/c8nr04842h
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structural design of exposed planes: express channels, high-rate capability cathodes for lithium-ion batteries

Abstract: Developing high-performance lithium ion batteries (LIBs) requires optimization of every battery component. Currently, the main problems lie in the mismatch of electrode capacities, especially the excessively low capacity of cathodes compared with that of anodes. Due to the anisotropy of the crystal structure, different crystal planes play different roles in the transmission of lithium ions. Among these, the {010} facets of layered-structure materials, the (110) planes of spinel cathodes and the (010) planes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(50 citation statements)
references
References 137 publications
1
47
0
2
Order By: Relevance
“…In addition to the phase structures and elemental composition, it has been found that the morphologies of Ni-rich cathodes especially the surface structures of the primary particles significantly affect the lithium intercalation kinetics. [126] The layered lithium transition metal oxide cathodes exhibited typical α-NaFeO 2 structure, in which lithium ions and TM cations occupy the octahedral sites of oxygen framework, forming a structure consisting of alternately stacked layers of MO 6 and LiO 6 octahedra. As shown in Figure 27, each layered perpendicular to the c axis is called (001) plane, which is electrochemically inactive due to the closely packed structure.…”
Section: Primary Particles Engineeringmentioning
confidence: 99%
“…In addition to the phase structures and elemental composition, it has been found that the morphologies of Ni-rich cathodes especially the surface structures of the primary particles significantly affect the lithium intercalation kinetics. [126] The layered lithium transition metal oxide cathodes exhibited typical α-NaFeO 2 structure, in which lithium ions and TM cations occupy the octahedral sites of oxygen framework, forming a structure consisting of alternately stacked layers of MO 6 and LiO 6 octahedra. As shown in Figure 27, each layered perpendicular to the c axis is called (001) plane, which is electrochemically inactive due to the closely packed structure.…”
Section: Primary Particles Engineeringmentioning
confidence: 99%
“…The particle size and microstructure infer a better charge capacity of the sample treated at 500 °C in relation to the sample treated at 700 °C because the sample at 500 °C presents pores and less sintering (greater surface area), thus facilitating the interface process associated with lithium diffusion. 58,59,65 It should be noted that recent works 13,58,59 report the importance of the preparation of LiMn 2 O 4 with specific morphologies, such as high porosity. In these works, the preparations involve several steps to obtain materials with the desired properties.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…The crystalline structure of LiMn 2 O 4 as well as the shape and size of the crystallites and grains are correlated with its electrochemical features. [11][12][13] The spinel LiMn 2 O 4 structure consists of compact cubic close packing composed by oxygen atoms that form 32 octahedral sites and 64 tetrahedral sites, as shown in Figure 1. 11 The Mn 3+ and Mn 4+ ions occupy the octahedral sites, whereas the Li + ion occupies the tetrahedral sites or the empty octahedral sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…open surface of {010} facets for layered, (110) planes for spinel, (010) planes for olivine facilitate the ion diffusion). 366 (ii) Surface area in the secondary particle: It has pros and cons. Large surface area leads to higher reaction rates, but can promote undesirable electrode/electrolyte reaction.…”
Section: Morphologymentioning
confidence: 99%